Genetic analysis of GEFs and GDIs in rice reveals the roles of OsGEF5, OsGDI1, and OsGEF3 in the regulation of grain size and plant height - Munsif Ali Shad; Yixian Wang; Hui Zhang; Shanshan Zhai; Abdullah Shalmani; Yibo Li (Crop Journal, 2023)
Guanine nucleotide exchange factors (GEFs) and guanine nucleotide-dissociation inhibitors (GDIs) regulate small GTPase proteins, which function as molecular switches in various signaling pathways, but their identification and functions in plants are not well understood. Using in-silico analysis and transgenic approaches, respectively, we dissected the evolutionary relationships and functions of all GEF and GDI genes in rice. Intron-exon distribution and phylogenetic analyses identified 30 GEF and 10 GDI genes in rice that shared close evolutionary relationships with other eukaryotes. Tissue-specific expression and co-expression analyses revealed that phylogenetically related genes had similar expression patterns. GEF and GDI genes were highly expressed in panicles, hulls, and stamens. Co-expression network analysis identified panicle and stamen-specific modules of co-expressed genes in both families. Mapping of these genes in known protein interactomes further identified two and one small G-protein sub-networks. A mutant library of GEF and GDI families was constructed by CRISPR knockout of each gene, and their genotypes and phenotypes were confirmed. Phenotype changes occurred with the mutation of only three genes (OsGEF5, OsGDI1, and OsGEF3). OsGEF5 and OsGDI1 single mutants exhibited significantly reduced height and longer and thinner grains, whereas OsGEF3 mutants had reduced grain length compared to the wild type. Haplotype and eGWAS analyses showed that natural variations in the three genes affected gene expression in reproductive tissues that were significantly associated with the phenotypic variation. BiFC assays demonstrated that GDI1 and GEF3 interacted with grain-size protein GS3, pointing to a role of these genes in the regulation of grain size and plant architecture connected to heterotrimeric G-proteins in rice.